On transfer factors of natural radionuclides and radiological health risks assessment of some fruit samples - Salh, Hemn; Sedeeq, Shalaw Zrar; Pehlivanoglu, Serpil Akozcan; Albarzinji, Ikbal M.; Kulahci, Fatih (Walter de Gruyter Gmbh, 2024)
In this study, the activity concentration of artificial and natural radionuclides such as 137Cs, 40K, 226Ra, and 232Th was measured in the soil under the roots; leaves; and fruits of six different fruit trees namely mulberry, fig, apricot, olive, black and white grapes in Koya district, Erbil province, Iraq. For this purpose, a high-resolution gamma spectroscopy consisting of a high-purity germanium (HPGe) detector was used. In addition, the associated radiological risks from soil and fruits were assessed by calculating several radiological indices such as radium equivalent (Raeq.s), absorbed dose (Ds), indoor (AEDEs indoor ) and outdoor annual effective doses (AEDEs outdoor ), internal and external hazard indices, gamma index and the excess lifetime cancer risk (ELRCs). The results show that consuming these fruits is radiologically safe because they can cause an annual effective dose of about 61.72 mu Sv y-1 and excess lifetime cancer risk of 0.06 x 10-3 Sv y-1. On the other hand, transfer factors of radionuclides from soil to leaves; and from soil to fruits were studied. The transfer factor analysis revealed that among the studied fruits and radionuclides, apricot and mulberry exhibited the highest transfer factors for 40K, with values of 1.85 and 1.87, respectively.
Keywords: activity concentration; HPGe detector; transfer factor; effective dose; radiological indices; cancer risk